MANAJEMEN PELATIHAN PENDIDIKAN NON-FORMAL STUDIO PERTUNJUKAN TARI TENTARA, SURABAYA - Nuria, Ananda (Solah, 2026)
Non-formal education plays a strategic role in developing students’ talents, interests, and character, particularly through arts-related activities. One form of non-formal education that contributes to dance education is the dance studio. This study aims to describe the management of non-formal education training at the Army Dance Performance Studio in Surabaya, focusing on the aspects of planning, organizing, implementation, as well as supervision and evaluation of the training program. The research employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The results indicate that training planning at the studio is conducted systematically through the determination of objectives, materials, and training programs tailored to the needs and developmental stages of the participants. The organizing process is characterized by a clear division of roles and responsibilities between the studio management and dance instructors. The implementation of the training program is carried out in accordance with the established plans, emphasizing the development of dance techniques, creativity, and character building among participants. Supervision and evaluation are conducted continuously through direct observation and assessment of participants’ skills. Overall, the training management applied at the Army Dance Performance Studio has a positive impact on improving the quality of the learning process and training outcomes, as well as supporting the sustainability of the studio as a non-formal education institution.